2019
DOI: 10.1128/aem.02814-18
|View full text |Cite
|
Sign up to set email alerts
|

Coculturing Bacteria Leads to Reduced Phenotypic Heterogeneities

Abstract: Isogenic bacterial populations are known to exhibit phenotypic heterogeneity at the single-cell level. Because of difficulties in assessing the phenotypic heterogeneity of a single taxon in a mixed community, the importance of this deeper level of organization remains relatively unknown for natural communities. In this study, we have used membrane-based microcosms that allow the probing of the phenotypic heterogeneity of a single taxon while interacting with a synthetic or natural community. Individual taxa we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 65 publications
(69 reference statements)
2
27
0
Order By: Relevance
“…Indeed, microbial identification and microbial interactions can be performed with a label-free Raman spectroscopy (Lorenz et al, 2017). In this area, a very refined investigation is dedicated to detect phenotypic heterogeneity of bacteria, where Raman spectroscopy offers advantages over flow cytometry (Heyse et al, 2019). Coating bacteria with inorganic noble metal nanoparticles facilitates the enhancement of the Raman scattering signal (Zhou et al, 2014).…”
Section: Hybrid and Composite Materialsmentioning
confidence: 99%
“…Indeed, microbial identification and microbial interactions can be performed with a label-free Raman spectroscopy (Lorenz et al, 2017). In this area, a very refined investigation is dedicated to detect phenotypic heterogeneity of bacteria, where Raman spectroscopy offers advantages over flow cytometry (Heyse et al, 2019). Coating bacteria with inorganic noble metal nanoparticles facilitates the enhancement of the Raman scattering signal (Zhou et al, 2014).…”
Section: Hybrid and Composite Materialsmentioning
confidence: 99%
“…These populations are known to exhibit considerable heterogeneity due to cell size diversity and cell cycle variations (Vives-Rego et al, 2003). Our research group has recently shown that the cytometric diversity of an individual population reduces when that population is part of a co-culture (Heyse et al, 2019). Therefore, data used for the in silico community creation setup cannot be used to study environmental samples, as we hypothesize that members of natural communities will have a different cytometric fingerprint as opposed to populations that were grown and measured individually.…”
Section: Discussionmentioning
confidence: 99%
“…The HC calculation developed in the present study for nanoSIMS-derived data, including CSE correction, were incorporated in the up-to-date version of the supplementary Excel template ( Supplementary Table S1). The developed HC expression can be applied as a measure of heterogeneity not only of cellular anabolic activity, but also of any parameter measured at the single-cell level within a population: for example, length, volume, fluorescence yield, and gene expression (Nikolic et al, 2013;Gangwe Nana et al, 2018;Simşek and Kim, 2018;Heyse et al, 2019). The supplementary Excel template was therefore extended for HC calculation on the data acquired with other single-cell-resolved techniques.…”
Section: Hc Applicability To Nanosims Datamentioning
confidence: 99%